Short Communication: Feeding trial, biological, and demographic parameters of Spodoptera frugiperda (Lepidoptera: Noctuidae) on several Graminae species (laboratory trial scale) - ANAK AGUNG AYU AGUNG SRI SUNARI; I WAYAN SUPARTHA; I WAYAN SUSILA; I WAYAN EKA KARYA UTAMA; I WAYAN SANDIKA YASA; I KADEK WISMA YUDHA (Society for Indonesian Biodiversity, 2023)
Abstract. Sunari AAAAS, Supartha IW, Susila IW, Utama IWEK, Yasa IWS, Yudha IKW. 2023. Short Communication: Feeding trial, biological, and demographic parameters of Spodoptera frugiperda (Lepidoptera: Noctuidae) on several Graminae species (laboratory trial scale). Biodiversitas 24: 3325-3331. The fall armyworm Spodoptera frugiperda J.E Smith is a new pest that has entered Indonesia. The ability of the S. frugiperda pest adaptation to several types of graminae plants is important to determine the distribution of potential hosts in the field. The adaptability of S. frugiperda was observed from two parameters, namely biology, and demography, which were tested on three plant types of the Graminae family consisting of hybrida variety corn, Jatiluwih local rice, and sorghum. This research was conducted from May to November 2022 at the Integrated Pest and Disease Management Laboratory (IPMLab), Faculty of Agriculture, Udayana University. The observation was made on several bionomic and demographic parameters. Demographic parameters were determined by observing the gross reproduction rate (GRR), net reproductive rate (R0), intrinsic rate of increase (r), generation time (T), doubling time (DT), and observing the fecundity rate of S. frugiperda. The results showed that S. frugiperda biology was best in hybrid corn plants with a short duration of larval life. The survival chances were obtained from daily observations of S. frugiperda, which decreased on day 32 on hybrid corn and sorghum plants. On the other hand, on Jatiluwih local rice plants, imago's survival chance started to decrease at 34 days old. In observing demographic parameters, lower R0 and r values and higher T and DT values ??indicate that hybrid corn plants are the best for S. frugiperda to grow and develop.